Loss-of-Function Piezo1 Mutations Display Altered Stability Driven by Ubiquitination and Proteasomal Degradation - Zhou, Zijing; Li, Jinyuan Vero; Martinac, Boris; Cox, Charles D. (Frontiers in Pharmacology, 2021)
Missense mutations in the gene that encodes for the mechanically-gated ion channel Piezo1 have been linked to a number of diseases. Gain-of-function variants are linked to a hereditary anaemia and loss-of-function variants have been linked to generalized lymphatic dysplasia and bicuspid aortic valve. Two previously characterized mutations, S217L and G2029R, both exhibit reduced plasma membrane trafficking. Here we show that both mutations also display reduced stability and higher turnover rates than wild-type Piezo1 channels. This occurs through increased ubiquitination and subsequent proteasomal degradation. Congruent with this proteasome inhibition using N-acetyl-l-leucyl-l-leucyl-l-norleucinal (ALLN) reduced the degradation of both mutant proteins. While ALLN treatment could not rescue the function of S217L we show via multiple complementary methodologies that proteasome inhibition via ALLN treatment can not only prevent G2029R turnover but increase the membrane localized pool of this variant and the functional Piezo1 mechanosensitive currents. This data in combination with a precision medicine approach provides a new potential therapeutic avenue for the treatment of Piezo1 mediated channelopathies.